Analisis Kepuasan Siswa Terhadap Layanan Administrasi di SMAN 10 Mataram - Faqih, M; Ridho, Rasyid; Permatasari, Anggita (Alpatih Harapan Semesta, 2023)
This study aims at determining: 1) the level of quality of administrative services, 2) the level of student satisfaction, and 3) the effect of the quality of administrative services on student satisfaction in SMAN 10 Mataram. The research approach used is quantitative with associative methods. The sample used in this study was 100 which were determined by stratified random sampling. Data were collected using the questionnaire method and then analyzed using descriptive statistics and simple linear regression analysis. The results of the analysis show that: 1) The quality of administration services at SMAN 10 Mataram is 3.27 which is in the very good category; 2) Student satisfaction at SMAN 10 Mataram is 3.24 which means that student satisfaction is high; and 3) The results of the regression analysis show: a.) There is a significant correlation between X and Y with a correlation coefficient of 0.657; b.) The regression equation obtained is Y = 0.824 + 0.740(X); c.) The regression model is a significant model based on the F-count value of 72.24 and a significance level of 0.000, d.) The effect of X and Y is a significant effect based on the t-count value of 8.616 and a significance level of 0.000; and e) The influence of X on Y is 43.1%.